Breast cancer with isolated metastatic temporomandibular joint: a surgeon’s challenge - Ho Hui Lian; Firdaus Hayati; Nornazirah Azizan; Andee Dzulkarnaen Zakaria (Penerbit UMS, 2018)
Breast cancer is the number one malignancy in women worldwide. It tends to metastasize distantly via lymphatic and haematogenous route. Skeletal metastases are frequent with more than three quarter of cases in all malignant bone tumours. Breast cancer can infiltrate the axial bone especially spine, but rarely affect the temporomandibular joint. In view of its rarity and the significance of early detection, the diagnosis is always challenging and shall be considered in the differential diagnosis. We endeavour to highlight this unfortunate 37-year-old lady who had just undergone left mastectomy and axillary dissection but was complicated with left temporomandibular joint metastasis.